Cp2k: atomistic simulations of condensed matter systems. (13th June 2013) - Hutter, Jürg; Iannuzzi, Marcella; Schiffmann, Florian; VandeVondele, Joost
<x xml:space="preserve">Abstract</x> <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>